2022
DOI: 10.1021/acsapm.2c00742
|View full text |Cite
|
Sign up to set email alerts
|

Deep Eutectic Solvent-Extracted Lignin as an Efficient Additive for Entirely Biobased Polylactic Acid Composites

Abstract: This work reports the fabrication and characterization of entirely biobased composites made with polylactic acid (PLA) and deep eutectic solvent (DES)-extracted lignin. White fir sawdust and corn stover were used as feedstocks to extract sawdust lignin (SDL) and corn stover lignin (CSL). Commercial alkali lignin (CAL) was also used as a baseline. PLA/lignin composites were fabricated using a twin-screw extrusion process followed by compression molding. Characterizations of the composites were conducted using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 49 publications
(98 reference statements)
0
10
0
Order By: Relevance
“…The composites also crystallize less, as the X c is smaller and decreases with an increased lignin content. The increase in T cc and the suppression of crystallinity are attributed to a reduced PLA chain mobility, caused by the interactions of the PLA with the lignin and its ability to absorb heat during heating, which prevents it from being absorbed by the PLA [ 21 , 26 , 27 , 28 , 29 ]. The small decrease in the T g was observed before [ 7 , 26 , 30 , 31 , 32 , 33 ] and it was attributed to the beneficial interactions between the lignin and the PLA, possibly by a plasticizing effect of a low molecular weight fraction of the lignin.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The composites also crystallize less, as the X c is smaller and decreases with an increased lignin content. The increase in T cc and the suppression of crystallinity are attributed to a reduced PLA chain mobility, caused by the interactions of the PLA with the lignin and its ability to absorb heat during heating, which prevents it from being absorbed by the PLA [ 21 , 26 , 27 , 28 , 29 ]. The small decrease in the T g was observed before [ 7 , 26 , 30 , 31 , 32 , 33 ] and it was attributed to the beneficial interactions between the lignin and the PLA, possibly by a plasticizing effect of a low molecular weight fraction of the lignin.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the reduction in the size of the particles after ball milling, with surfactants, seemed to positively affect the mechanical properties of the final materials [ 21 , 37 ]. On the other hand, the use of deep eutectic solvents exhibited a drop in the tensile features of the PLA [ 26 ]. Thus, the presented data is in accordance with the literature, showing the advantages of using low percentages of unmodified lignin and avoiding additional energy and time-consuming procedures.…”
Section: Resultsmentioning
confidence: 99%
“…Even though many publications on PLA-lignin composites are available, most of them do not mention the particle size of lignin and disregard its effect on the obtained results. A few studies have demonstrated that size reduction of lignin from the microscale to sub-micron particles helps achieve better reactivity and compatibility with PLA due to the high specific surface area and better dispersion ability, which allows it to bond more effectively with the PLA matrix [ 5 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. In all cases, the composites were prepared by either melt mixing or solution casting.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(lactic acid) (PLA) can be derived from green resources such as wheat, sugarcane, and corn through biofermentation. 19,20 It is currently one of the most desirable bio-based polymers due to its favorable mechanical performance, biocompatibility, biodegradability, and low production cost. 21,22 The market value of PLA is projected to reach approximately 1.82 billion U.S. dollars in 2028, approximately 3.5 times its market value in 2020.…”
Section: Introductionmentioning
confidence: 99%
“…Poly­(lactic acid) (PLA) can be derived from green resources such as wheat, sugarcane, and corn through biofermentation. , It is currently one of the most desirable bio-based polymers due to its favorable mechanical performance, biocompatibility, biodegradability, and low production cost. , The market value of PLA is projected to reach approximately 1.82 billion U.S. dollars in 2028, approximately 3.5 times its market value in 2020 . However, the limited toughness, slow crystallization rate, and poor heat resistance of PLA significantly restrict its application. Similarly, PCL is broadly applied in packaging and biomedical fields due to its flexibility, processing properties, biocompatibility, and biodegradability. , …”
Section: Introductionmentioning
confidence: 99%